Characterization of vibrio alginolyticus isolated from white leg shrimp (Litopenaeus vannamei) with emphasis on its antibiogram and heavy metal resistance pattern - Lee Seong Wei; Wee Wendy (2012)
This paper describes the antibiogram and heavy metal resistance pattern of Vibrio alginolyticus isolated from farmed white leg shrimp (Litopenaeus vannamei). V. alginolyticus has been recognized as a causative agent of vibriosis in shrimp culture and can devastate an entire shrimp farm. Therefore, this study was carried out to investigate the suitability of using antibiotics against V. alginolyticus, as well as its tolerance to heavy metals, to reveal the exposure level of cultured shrimp to heavy metals. In the present study, a total of 14 antibiotics; oxolinic acid (2 μg), ampicillin (10 μg), erythromycin (15 μg), furazolidone (15 μg), lincomycin (15 μg), colistin sulphate (25 μg), oleandomycin (15 μg), doxycycline (30 μg), fosfomycin (50 μg), fl orfenicol (30 μg), fl umequine (30 μg), tetracycline (30 μg), fosfomycin (50 μg) and spiramycin (100 μg) as well as four heavy metals; mercury (Hg2+), cadmium (Cd2+), chromium (Cr6+) and copper (Cu2+) were applied. Based on the results for antibiotic sensitivity, it was shown that oxolinic acid is the most effective antibiotic in controlling V. alginolyticus, where 92.8% of the bacterial isolates present were sensitive to it. It was followed by furazolidone (85.6%), nitrofuratoin (79.8%), tetracycline (78.8%), doxycycline (72.2%) and fl orfenicol (71.2%). On the other hand, all the bacterial isolates present were resistant to lincomycin. In the heavy metal tolerance test, all the bacterial isolates present were resistant to Hg2+, Cd2+ and Cr6+ whereas only 26.7% of them were resistant to Cu2+.